Allocybaeina littlewalteri (Araneae: Cybaeidae): a new genus and species endemic to northwestern California - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2020)
Various undescribed Cybaeina Chamberlin & Ivie (Araneae: Dictynoidea: Cybaeidae) and Cybaeina-like taxa are known from forested habitats in the west coast of North America. Most have very restricted ranges within the northern portion of the Californian Floristic Province, a well-known biodiversity hotspot. Here we describe Allocybaeina Bennett gen. nov. and its single included species, Allocybaeina littlewalteri Bennett spec. nov. This infrequently collected species is restricted to forested habitat in a small area of the coastal watersheds of southern Humboldt and western Mendocino Counties in northwestern California, U.S.A. In addition to descriptions we provide diagnoses, illustrations, a distribution map, and discuss conservation implications for this distinctive new genus and species.